If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying J + -964 = 3 Reorder the terms: -964 + J = 3 Solving -964 + J = 3 Solving for variable 'J'. Move all terms containing J to the left, all other terms to the right. Add '964' to each side of the equation. -964 + 964 + J = 3 + 964 Combine like terms: -964 + 964 = 0 0 + J = 3 + 964 J = 3 + 964 Combine like terms: 3 + 964 = 967 J = 967 Simplifying J = 967
| -28=-8w+2(w+7) | | x+36+60+90=180 | | 3x+5=212 | | x+36+60=180 | | 11=x-11 | | 3(u-5)=7u-35 | | 8y-[2y-3]=9 | | 1/2x-5/6=1/6 | | -7(y-3)=-9y+15 | | -2w+8=-7(w-4) | | x+94+40+50=180 | | 5y+3=26 | | 3v+4=6+19 | | 2/3l-1/3=-5/9 | | -26=2(y-7)-5y | | Jk=5(x-2)JL=6x+30 | | -5w-8=-3(w+8) | | -8h+2=6h-5 | | (y-6)-(y+2)=26 | | Ln(8x-4)=1 | | -7w+4(w+6)=30 | | 12x=7000 | | -3w+2=-10w+3 | | 3.2-x=4.2 | | 6m+7=30-m | | 6(d+61)=744 | | 5/7=p=4/7 | | 18=3(u-4)-6u | | 6m+7=30+m | | 9y=12+6y | | L=1584/6×8 | | 14/13=d/48 |